[18F]fluorothymidine and [18F]fluorodeoxyglucose PET Imaging Demonstrates Uptake and Differentiates Growth in Neurofibromatosis 2 Related Vestibular Schwannoma. Issue 6 (July 2019) - Anton-Rodriguez, Jose M.; Lewis, Daniel; Djoukhadar, Ibrahim; Russell, David; Julyan, Peter; Coope, David; King, Andrew T.; Lloyd, Simon K. L.; Evans, D. Gareth; Jackson, Alan; Matthews, Julian C.
Abstract : Objective: To investigate whether [ 18 F]fluorothymidine (FLT) and/or [ 18 F]fluorodeoxyglucose (FDG) positron emission tomography (PET) can differentiate growth in neurofibromatosis 2 (NF2) related vestibular schwannomas (VS) and to evaluate the importance of PET scanner spatial resolution on measured tumor uptake. Methods: Six NF2 patients with 11 VS (4 rapidly growing, 7 indolent), were scanned with FLT and FDG using a high-resolution research tomograph (HRRT, Siemens) and a Siemens Biograph TrueV PET-CT, with and without resolution modeling image reconstruction. Mean, maximum, and peak standardised uptake values (SUV) for each tumor were derived and the intertumor correlation between FDG and FLT uptake was compared. The ability of FDG and FLT SUV values to discriminate between rapidly growing and slow growing (indolent) tumors was assessed using receiver operator characteristic (ROC) analysis. Results: Tumor uptake was seen with both tracers, using both scanners, with and without resolution modeling. FDG and FLT uptake was correlated (R 2 = 0.67–0.86, p < 0.01) and rapidly growing tumors displayed significantly higher uptake (SUVmean and SUVpeak ) of both tracers ( p < 0.05, one tailed t test). All of the PET analyses performed demonstrated better discriminatory power (AUCROC range = 0.71–0.86) than tumor size alone (AUCROC = 0.61). The use of standard resolution scanner with standard reconstruction did not result in a notable deterioration of discrimination accuracy. Conclusion: NF2 related VS demonstrate uptake of both FLT and FDG, which is significantly increased in rapidly growing tumors. A short static FDG PET scan with standard clinical resolution and reconstruction can provide relevant information on tumor growth to aid clinical decision making. Abstract : Supplemental Digital Content is available in the text